The Role of the Yogyakarta Community Early Warning Forum in Supporting the National Defense - Daru Putri Kusumaningtyas; Firda Nur Isnaini (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2023)
This study aims to explain the role of the Yogyakarta City Government in forming the Community Early Warning Forum (Forum Kewaspadaan Dini Masyarakat or FKDM) in supporting the national defense. The city of Yogyakarta currently has various problems that, if not detected early on, will threaten Indonesia. To anticipate existing threats, the Yogyakarta City Government established the FKDM. The formation of FKDM in Yogyakarta is by the policies, strategies, and development of national defense capabilities listed in the Defense White Paper. So, FKDM plays an important role in supporting national defense and preventing threats. This study uses a qualitative method. The results of the study found that Yogyakarta City's FKDM has played a role in supporting national defense, namely by carrying out early vigilance even though in carrying out its role Yogyakarta City's FKDM has not been maximized because of its capabilities and capacity. Members of FKDM and classification of threats in a report format that is not by the non-military threats listed in the national defense posture book. Because Yogyakarta City FKDM has not been optimal in carrying out its role, it is necessary to classify the types of threats according to the national defense posture book; retraining members of Yogyakarta City FKDM as well as sub-district FKDM and village FKDM in Yogyakarta City regarding the forms of threats; to maximize the use of the Lapak Deni application, it is necessary to consider age when recruiting FKDM members; as well as the need for additional personnel from the teaching staff by the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 46 of 2019 concerning Amendments to Minister of Home Affairs Regulation Number 2 of 2018 concerning Early Alertness in the Regions, article 16 paragraph (3).